A Politik Hukum Disseting Opinion Pengujian UU Terhadap UUD 45 Dalam Rangka Mencari Kebenaran Hukum: Peran Dissenting Opinion dalam Putusan Mahkamah Konstitusi: Perspektif Hakim dan Penafsiran Hukum - Zaman, Nurus (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The dissenting opinion of Constitutional Court judges in conducting judicial reviews of laws against the 1945 Constitution represents the freedom of Constitutional Court judges. These dissenting opinions are essentially aimed at seeking legal truth. This research addresses two main issues: First, the legal politics behind the occurrence of dissenting opinions by Constitutional Court judges in reviewing laws against the 1945 Constitution. Second, the methods of legal interpretation used by Constitutional Court judges in reviewing laws against the 1945 Constitution. This study uses normative legal methods, with statutory and conceptual approaches. The findings of this research are as follows: First, the provisions of Article 24, paragraphs (1) and (2) of the 1945 Constitution provide the constitutional basis for the dissenting opinions of Constitutional Court judges in reviewing laws against the 1945 Constitution. Second, Constitutional Court judges are not restricted nor bound by any single method of legal interpretation. The use of legal interpretation methods by Constitutional Court judges in reviewing laws against the 1945 Constitution is their prerogative, as, in principle, the use of such methods is aimed at seeking legal truth.